The implications of the CAP reform for ACP-EU agricultural trade (CTA WageningenNL, 2009)
Reviews the scope of the Common Agricultural Policy i.e. its basic structure, product coverage, objectives and evolution since 1992.
Keywords: AGRICULTURAL POLICY